2018
DOI: 10.1002/nafm.10039
|View full text |Cite|
|
Sign up to set email alerts
|

Pulse Trawling: The Impact of Pulsed Direct Current on Early Life Stages of Sole Solea solea

Abstract: Despite electric pulse fishing being regarded as a promising environmentally friendly fishing method, very little is known about possible negative effects on early life stages of bottom‐dwelling species such as Sole Solea solea. Electrotrawling for brown shrimp Crangon crangon is increasingly used in shallow coastal zones and estuaries of the southern North Sea. As these fishing grounds are often important nurseries and spawning areas for various marine species, electrotrawling could therefore harm inhabiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…No studies are available on the impact of the sole pulse on early life stages, but two studies exposed early life stages of cod and sole for 5 s to a squarewave PDC of 150 V m −1 and a lower frequency (5 Hz) with ambiguous results (Desender et al 2017a(Desender et al , 2018. In cod, an increased mortality was reported in two out of eight egg and larval stages tested, whereas no effect was found in sole.…”
Section: Impact On Eggs and Larvaementioning
confidence: 99%
“…No studies are available on the impact of the sole pulse on early life stages, but two studies exposed early life stages of cod and sole for 5 s to a squarewave PDC of 150 V m −1 and a lower frequency (5 Hz) with ambiguous results (Desender et al 2017a(Desender et al , 2018. In cod, an increased mortality was reported in two out of eight egg and larval stages tested, whereas no effect was found in sole.…”
Section: Impact On Eggs and Larvaementioning
confidence: 99%
“…A laboratory study found an increased mortality in early life stages (pelagic eggs, larvae) of cod that were exposed to a shrimp pulse with a comparable field strength but lower pulse frequency (Desender et al, 2017a). A similar experiment with sole eggs and larvae did not find any adverse effects (Desender et al, 2018). Potential population level consequences of pulse induced mortality among pelagic eggs and larvae was explored by estimating the proportion of the eggs and larvae that are exposed to pulse trawling.…”
Section: 3)mentioning
confidence: 99%
“…They found effects on survival and development for two out of eight developmental stages, and conclude that delayed hatching and deceased survival of larvae might indicate an effect of the stimulus. Hereafter, Desender et al (2018) found no effect in a similar exposure experiment on short-term mortality, deformations, reduced growth, and yolk-sac resorption of common-sole embryos and larvae. Natural mortality of fish larvae is, however, high as the vast majority die before reaching the juvenile stage, often due to starvation Houde, 2002).…”
Section: Marine Fishesmentioning
confidence: 80%
“…This sparked a new wave of research focusing -again -on fuel consumption, catch efficiency, and selectivity ; van Marlen et al, 2006van Marlen et al, , 2014; Steenbergen and Verschueren et al, 2019Verschueren et al, , 2012Turenhout et al, 2016; as well as economic investment theory (Jensen et al, 2019). In addition, environmental aspects were studied including discard survival (van Marlen et al, 2005;Schram and Molenaar, 2018), potential negative effects of electrical stimulation on marine organisms (van Marlen et al, 2001(van Marlen et al, , 2007(van Marlen et al, , 2009bde Haan et al, 2009bde Haan et al, , 2009ade Haan et al, , 2011de Haan et al, , 2013Desender et al, 2018Desender et al, , 2017aDesender et al, , 2017b, physical benthic disturbance , spatio-temporal fleet distribution (Sys et al, 2016;Turenhout et al, 2016), effects on a larger, ecological scale (Stepputtis et al, 2014;Teal et al, 2014;Ford et al, 2019;Vansteenbrugge et al, 2020), and, in some instances, how to minimise any negative effects by e.g. choosing other electrical waveform parameters .…”
Section: (A) (B) (C)mentioning
confidence: 99%